Performance Optimization Analysis of a 20 Kilo Volt (kV) Distribution Network in Dili City Using ETAP Software - Zil Nunes Pinto; Herry Nugraha; I Made Indradjaja M. Brunner (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
The 20 kV power distribution network in Dili City faces technical challenges in the form of voltage drop and relatively high feeder loading levels, particularly on feeders with long distribution routes. The Dili City distribution network has a configuration centralized to a single power supply source, namely the Camea Substation, which limits the ability to transfer loads. This research aims to analyze the existing condition and to evaluate the effect of adding a new substation in the Comoro area on improving network performance. This research uses a power flow simulation–based approach employing ETAP software. The results show that under existing conditions, buses at the end of the lines experience voltage drops below the allowable standard of up to 14.30%, and four feeders have loading levels exceeding 75%. The addition of the Comoro Substation and network reconfiguration significantly improve the voltage profiles of the distribution system, ensuring compliance with SPLN 72:1987. The loading level of the Camea Substation decreases to 72% of its capacity due to the reduction of feeder load, increasing the capability for load transfer and accommodating future load growth.